HUBUNGAN ANTARA BRAND TRUST DENGAN CUSTOMER ENGAGEMENT PADA MAHASISWI PENGGUNA WARDAH KOSMETIK - ROSTIKA ADI SUKAMDEWI; Unika Prihatsanti (Faculty of Psychology, Diponegoro University, 2017)
The competition of cosmetics industry demands companies to increase customer engagement of the products. Customer engagement is a process that involves physical presence , cognitive and emotional that are confronted by having relation with brand and brand service. Customer who has brand trust will be fulfilled with trust and security of the brand. The purpose of this research is to analyze the relationship between brand trust and customer engagement. The population were the students of Psychology Department of UNDIP. The samples were 70 female who used Wardah cosmetic. Sampling purposive technique was used in this research. The data were collected using Brand Trust Scale (27 aitem, α = .91) and Customer Engagement Scale (24 aitem, α = .92). The result shows that correlation coefficient (rxy) = .73 with p <.05. These results indicate that the hypothesis was proposed, there is a significant positive relationship between brand trust with customer engagement. The higher the brand trust, the higher customer engagement. Brand trust contributes effectively of 53 % to customer engagement.